Upaya Meningkatkan Hasil Belajar Siswa pada Materi Organ Gerak Hewan dan Manusia Melalui Metode Demonstrasi di Kelas V MIN 4 Langkat - Emha Fidiyan Akhadi; Indra Syah Putra; Wahyuni Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2023)
This classroom action research was carried out to improve the learning process which was not yet optimal and the low learning outcomes in class V of SD Negeri Marga Cinta Kab. East Oku. This research aims to evaluate the effect of applying the demonstration method on students' understanding and learning outcomes regarding science subjects regarding animal and human movement organs. Implementation of improvements was carried out in two cycles, namely Cycle I on 06 May 2022 and Cycle II on 08 May 2022. In Cycle I, there were several problems that arose during the learning process so that the expected goals were not achieved optimally. Only 63.6% of the student data obtained scores above the requirements for completeness or (KKM). However, in Cycle II, the learning process becomes more conducive and the expected goals can be achieved well. The demonstration method has succeeded in increasing students' enthusiasm, activeness and learning outcomes very satisfactorily, achieving a success percentage of 100%. This shows that the application of the demonstration method effectively increases students' understanding and learning outcomes in the science subject material on animal and human movement organs in class V of SD Negeri Marga Cinta Kab. East Oku. These results indicate that the demonstration method can be an effective alternative in improving student learning outcomes in animal and human movement organs.